Comparison of KMO Results, Eigen Value, Reliability, and Standard Error of Measurement: Original & Rescaling Through Summated Rating Scaling - Astuti, Nuryani Dwi; Hajaroh, Mami; Prihatni, Yuli; Setiawan, Ari; Setiawati, Farida Agus; Retnawati, Heri (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to compare the results of KMO MSA analysis, Eigen Value, reliability, and Standard Error Measurement (SEm) between raw scores (original) and standardized scores (rescaling) through the summated rating scaling method on critical reasoning attitudes of vocational students in Yogyakarta City. This study used a quantitative descriptive approach involving 204 private vocational students as subjects. The instrument used to measure critical reasoning attitudes has gone through thorough validity and reliability testing before the research was carried out. The analysis process was carried out by calculating the KMO MSA, Eigen Value, reliability, and SEm values on both raw and standardized scores. The results of the two types of scores were then compared to identify any differences. Based on the results of the analysis, it was found that the raw score had a KMO MSA of 0.87, reliability of 0.823, and SEm of 0.337. After rescaling, the KMO MSA value decreased slightly to 0.86, the reliability also decreased slightly to 0.821, while the SEm increased to 0.406. Eigenvalue analysis showed that both the raw and standardized scores yielded seven factors with Eigenvalues greater than 1. The differences found between these two types of scores, namely 0.01 for KMO MSA, 0.002 for reliability, and -0.069 for SEm, indicate small but significant changes, especially in terms of the increase in SEm after rescaling, which impacts the level of measurement accuracy.